Atalante and Hippomenes: Iconographic Recreation of a Myth - Rodríguez López, María Isabel (Eikón / Imago, 2018)
Taking as a pretext the beautiful painting by Guido Reni housed at the Prado Museum, we will look back at the ancient world to delve into the origin of the myth and the literary and iconographic antecedents that served as a preamble to the work of the Bolognese painter. We will also highlight the influence of Reni in the following art and how Western painting was deeply influenced by his masterpiece, which has since become an iconic paradigm of the motif until present day.